Proverbs as an object of contrastive linguistics and lingual didactics - Muxammadiyeva, Madinabonu (The Lingua Spectrum, 2025)
This article provides a comprehensive analysis of English and Uzbek proverbs from linguistic, cultural, cognitive, and pragmatic perspectives, highlighting their didactic value in contemporary language education. Drawing on the works of Abdullayeva, Normurodova, Gadoyeva, Qambarova, Eshonkulova, Boykhanov, and Alibekova, the study examines the conceptual structure of proverbs, their metaphorical foundations, their role in reflecting national mentality, and their functions within intercultural communication. The semantic layers of proverbs, their stylistic potential, contextual meanings, and pragmatic functions within various speech acts are explored in detail. The article emphasizes that proverb-based instructional tasks foster learners’ cultural awareness, pragmatic adaptability, communicative competence, and lexical development. Furthermore, such activities stimulate creative thinking, deepen understanding of cultural realities, and enhance the naturalness and expressiveness of speech. The findings confirm that proverbs, as unique linguocultural units integrating language and culture, hold significant importance within modern integrative teaching methodologies and contribute to shaping linguistically competent and culturally sensitive learners.